ANALISIS SISTEM PENGENDALIAN INTERNAL PENGELOLAAN PERSEDIAAN PADA PT. SUPIM DELI PERKASA - Sanjaya, Rudi; Nurhayati, Nurhayati; Mulyani, Sri (Worksheet : Jurnal Akuntansi, 2023)
This study aims to find out how the internal control system is in inventory management and whether theapplication of the internal control system in inventory management at PT. Supim Deli Perkasa cansupport the effectiveness of inventory control. The data used in this study is qualitative with adescriptive approach. The results of the study show that internal control at PT. Supim Deli Perkasa hasnot been implemented optimally and regarding inventory management it is still vulnerable to dangerand risk, because from purchasing procedures, storing goods, recording to selling merchandise, thecompany still uses semi-manual data entry. PT. Supim Deli Perkasa in managing inventory is stillexperiencing several problems including the difference in the amount of inventory, still using manualrecording which allows errors when calculating and recording inventory, damage to goods, due toinventory buildup. The Internal Control System is immediately implemented optimally by means of theneed for additional employees, so that there is no duplication of tasks and it is hoped that the method ofrecording inventory management in the future will already use a software-based whole. Have to dostock taking regularly and continuously, for items that run out faster or are often sold, you have to do astock count every day or every week and for items that are rarely sold, you can do a stock take every 1month and it is expected that from the employee’s point of view, you have to be more thorough whenrecording incoming and outgoing goods.